Psychosocial beliefs of health providers' intention and behavior of offering HIV testing and counseling services: Estimating their relevance for intervention - Almutaz Mohammed Idris; Almutaz Mohammed Idris; Rik Crutzen; Hubertus W. Van Den Borne (Frontiers Media S.A., 2022)
BackgroundDiagnosis of people with HIV is vital in achieving the 95-95-95 global targets. The proportion of people with HIV who know they have HIV in Sudan is low. Promoting engagement of healthcare providers (HCPs) in offering HIV Testing and Counseling (HTC) services would improve the percentage of diagnosed people with HIV in the country. This study aims to assess the psychosocial beliefs associated with HCPs' intention and behavior to offer HTC services and their relevance for intervention.MethodsThis institutional cross-sectional study was conducted in Kassala State, from July 2019 to February 2020, among 438 healthcare providers from public health facilities. A self-administered questionnaire was used to assess behavior and intention to offer HTC services and related behavioral, normative, and control beliefs. Data were analyzed using R software. Confidence Interval Based Estimation of Relevance (CIBER) was used to estimate the relevance of the beliefs to interventions.ResultsThe CIBER analysis showed that the belief "It causes many worries for patients if I offer or counsel them about HIV test" was negatively associated with HCPs' intention and behavior to offer HTC services and a highly relevant belief for intervention. The belief "My manager thinks I should offer or counsel patients about HIV test" was positively associated with the behavior and intention to offer HTC services and was a relatively highly relevant belief. The control belief "Patients are at low risk of HIV and do not need offering or counseling about HIV test" was negatively associated with HCPs' intention and behavior and was relevant for intervention. The control belief "If I offered or counseled patients about HIV test, I would spend more time with them" was negatively associated with the intention and behavior of HCPs toward HTC services, with high relevance to target with intervention. The belief "My colleagues think I should offer or counsel patients about HIV test" was weakly associated with behavior and intention, and it is a low relevant belief for intervention.ConclusionDifferent psychosocial beliefs among healthcare providers can influence their intention and behavior to offer HTC services to patients. More relevant beliefs are required to be targeted with interventions to promote the intention and behavior of providing HTC services among health care providers.